2009
DOI: 10.4278/ajhp.07072574
|View full text |Cite
|
Sign up to set email alerts
|

Risk Perception and its Association with Cardiac Risk and Health Behaviors among Urban Minority Adults: The Bronx Coronary Risk Perception Study

Abstract: PURPOSE To examine the relationship between risk perceptions, health behaviors, and a measure for actual risk of coronary heart disease (CHD). DESIGN Cross-sectional survey. SETTING/SUBJECTS Adults from three outpatient medical clinics with at least one CHD risk factor. MEASURES Perceived risk using the new Coronary Risk, Individual Perception (CRIP) scale, an index of CHD risk, and summary scores for self-reported diet and exercise. ANALYSIS Bivariate associations using Spearman Rank and Kruskil-Walli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 9 publications
3
29
1
Order By: Relevance
“…Blue-collar workers in the high CVD risk group perceived they were vulnerable and susceptible to CVD. Several studies that incorporated actual risk and perceived risk (Barnhart et al, 2009;Christian et al, 2005;Frijling et al, 2004;Homko et al, 2008) were identified. Of these, three studies used the Framing- showed an association between CVD risk and CVD risk perception.…”
Section: Discussionmentioning
confidence: 99%
“…Blue-collar workers in the high CVD risk group perceived they were vulnerable and susceptible to CVD. Several studies that incorporated actual risk and perceived risk (Barnhart et al, 2009;Christian et al, 2005;Frijling et al, 2004;Homko et al, 2008) were identified. Of these, three studies used the Framing- showed an association between CVD risk and CVD risk perception.…”
Section: Discussionmentioning
confidence: 99%
“…It is helpful in the risk dialogue or during patient consultation or counselling 2. Knowing patients’ concerns and how patients perceive their risk are important initial steps in appropriately managing the risk 3 4.…”
Section: Introductionmentioning
confidence: 99%
“…61 However, patient perception of actual risk often differs from modelpredicted risk. [62][63][64] If clinician-perceived risk also differs from model-predicted risk, the potential for systematic distortion in patient selection exists. Our hope is that clinicians' benevolence and fiduciary responsibilities toward patients drive them to always consider an individual patient's best interest.…”
Section: Unintended Consequences Of Public Reportingmentioning
confidence: 99%